2000
DOI: 10.1086/317289
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Entropy Excess in Clusters and Groups of Galaxies without Additional Heating

Abstract: The X-ray luminosity and temperature of clusters and groups of galaxies do not scale in a self-similar manner. This has often been interpreted as a sign that the intracluster medium has been substantially heated by nongravitational sources. In this Letter, we propose a simple model that instead uses the properties of galaxy formation to explain the available observations. Drawing on available observations, we show that there is evidence that the efficiency of galaxy formation was higher in groups than in clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
172
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(201 citation statements)
references
References 38 publications
26
172
3
Order By: Relevance
“…In the pioneering work of Bryan (2000), an overall agreement between the predicted and observed L X -T relations and entropy distributions has been essentially found, although at low temperature T < 1 keV, the observed L X -T relation falls below the theoretical prediction. Motivated by these successes and their profound implications for our understanding of the formation and evolution of the galaxies and gas in groups and clusters, we wish to conduct an extensive comparison of the theoretically predicted properties of the intragroup/intracluster gas by the GG model with those revealed by current X-ray observations.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the pioneering work of Bryan (2000), an overall agreement between the predicted and observed L X -T relations and entropy distributions has been essentially found, although at low temperature T < 1 keV, the observed L X -T relation falls below the theoretical prediction. Motivated by these successes and their profound implications for our understanding of the formation and evolution of the galaxies and gas in groups and clusters, we wish to conduct an extensive comparison of the theoretically predicted properties of the intragroup/intracluster gas by the GG model with those revealed by current X-ray observations.…”
Section: Introductionmentioning
confidence: 71%
“…Based on three independent studies of 33 groups and clusters in the literature, Bryan (2000) derived the following empirical formula, regardless of the large scatter of the data points especially for low-temperature groups: …”
Section: Reexamination Of the Working Hypothesismentioning
confidence: 99%
“…Again, the former result is well known (e.g. Bryan 2000;Muanwong et al 2001), being due to the effect of cooling removing the dense, low-entropy gas. However, this effect produces density (or entropy) profiles with the wrong shape: the density is too low beyond the core and too high in the centre.…”
Section: The L Bol -M 500 Relationmentioning
confidence: 81%
“…When radiative cooling is included, the entropy profile can be modified. Using a simplified model, Bryan (2000) argued that because rapid cooling always happens in lowentropy gas, and the high-entropy gas will expand adiabatically to occupy the volume of the halo, resulting in a flatter entropy profile. However, Tang et al (2009) found that cooling in Milky Way sized halos is a runaway process in their simulations, and the resulting entropy profile remains a power-law.…”
Section: Configuration Of the Hot Halo Gasmentioning
confidence: 99%